Myoxocephalus niger ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Myoxocephalus niger (Bean, 1881). Warthead Sculpin. To 27 cm (10.6 in) TL (Mecklenburg et al. 2002). Coasts of Sea of Okhotsk, and northern Sea of Japan to Commander–Aleutian Chain, and Pribilof Islands, southern Bering Sea to Sanak and Shumagin Islands, western Gulf of Alaska (Mecklenburg et al. 2002). Benthic; depth: intertidal to 50 m (164 ft) (min.: Mecklenburg et al. 2002; max: Federov et al. 2003). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 123, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...